Clinical Characteristics of Trichotillomania with Trichophagia - Grant, Jon E. (2008)
OBJECTIVE: Little is known about trichophagia in individuals with trichotillomania. Although studies have mentioned the behaviour, no previous studies have examined clinical correlates of trichophagia. METHOD: We examined the clinical correlates of trichophagia in 68 subjects with DSM-IV trichotillomania (85.3% females; mean age = 35.0 ± 12.5). Comorbidity data were obtained with the Structured Clinical Interview for DSM-IV. Trichotillomania severity was assessed with the Psychiatric Institute Trichotillomania Scale and the Massachusetts General Hospital Hairpulling Scale. Social/occupational functioning was examined using the Sheehan Disability Scale. All variables were compared in trichotillomania subjects without and without trichophagia. RESULTS: Of the 68 trichotillomania subjects, 14 (20.6%; 95% CI [12.7%-31.6%]) reported current trichophagia, and an additional 9 (13.2%) ate their hair or the root episodically. There were far more similarities than differences in trichoillomania subjects with current trichophagia and those without, although those with trichophagia were significantly more likely to be male (p=.013) and have more severe trichotillomania (according to the Massachusetts General Hospital Hairpulling Scale) (p=.010). CONCLUSIONS: These preliminary results suggest that trichophagia is not uncommon in individuals with trichophagia. Subjects with and without trichophagia were similar in most domains that were examined.